Comparison of training activities and coaching behaviours in youth football coaches from Spain and China: a case study - Feng, R.; Gomez-Ruano, M. A.; Liu, T.; Li, C.; Garcia-de-Alcaraz, A. (International Journal of Performance Analysis in Sport, 2023)
Youth football training should ensure proper player development. However, coaches worldwide behave differently during their coaching process. Thus, this study aims to: a) compare the coaching behaviour and training activities of the football coaches from China and Spain, and b) explore the impact of different pedagogy on coach`s behaviour and players` perceptions. Systematic observations and semi-structured interviews were developed for 6 youth coaches from Madrid (n = 3) and Beijing (n = 3). And 16 players randomly selected from each academy were queried their perception. The results showed significant differences in coaching behaviours and training activities between both groups. Madrid coaches used more "playing form" (PF) and achieved greater times of activation (motor participation) during practices, compared to Beijing coaches. Concurrent-instruction was the most used behaviour among coaches from both groups. Moreover, Madrid coaches applied more "positive feedback" whereas Beijing coaches used more "negative feedback". This phenomenon is related to different educational and pedagogical backgrounds. Positive feedback is recommended to Beijing coaches and "silence" should also be properly used while "instruction" and "hustle" should be carefully used to help players learn to "think" (e.g. decision-making). This study offers a comparative analysis to develop proper strategies for a better player`s development.